Nas encruzilhadas do Axé: experiências e representações de gênero e sexualidade em um terreiro de Candomblé Angola no centro-oeste brasileiro - RAFAEL MASCARENHAS MATOS (2022)
This work discuss gender experiences and sexuality in a Candomblé Angola house, which is located in Campo Grande, capital of Mato Grosso do Sul, Brazil. The Candomblé is a religion derived from traditions of African people, who were enslaved in Brazil, and arrived here through the slave trade. The divine Candomblé pantheon has a variety of masculinities and femininities representations and in some opportunities; the masculine/feminine binarism is suspended or broken. Considering, the Brazilian reality of exclusion and violence suffered by lesbians, gays, bisexuals, transsexuals, transvestites, intersex, asexuals and other people who have any variability of gender or sexual orientation (LGBTQIA+); and reports of reception of these same population in Candomblé terreiros, we are seeking understanding these relationships from ethnographic immersion in Abassa Maza N'Dandalunda. Starting from decolonial epistemologies and macumba, in a Cultural Studies field. Thus, we may understand the terreiro internal relationships; the identities, which are, not conform to gender binarity and with compulsory heterosexuality; the representations of the divine pantheon based on genres and singularities of gender arrangements within the researched house.